Predisposing factors for hypoglycaemia in the emergency department. Issue 6 (June 2019) - Su, Yu-Jang; Liao, Chia-Jung
Objective: Hypoglycaemia is a common complication of diabetes mellitus. Previous studies suggest that hypoglycaemic episodes may occur with other comorbidities, influencing the outcome of recovery. Recognising the predisposing factors for hypoglycaemic episodes in the emergency department is important. Therefore, we investigated the characteristics of and predisposing factors for hypoglycaemia in the emergency department. Methods: Data from 186 patients were retrospectively collected from a medical centre in northern Taiwan. We divided the patients into the advanced-age group (132 patients) and the younger group (54 patients). Associated data collected for statistical analysis included vital signs on arrival, first measured blood glucose level, laboratory results, related comorbidities, length of hospital stay, and survival to discharge. Results: Hypoglycaemia was more frequently observed in women in the advanced-age group than in the younger group. Tachycardia and elevated systolic blood pressure were less predominant in the advanced-age group than younger group. More patients in the advanced-age group had concurrent infection, and more patients in the younger group had liver dysfunction, elevated liver enzymes, liver cirrhosis, and concurrent stroke. Conclusions: Closer attention should be paid to the possibility of infection in patients of advanced age. Liver disease and stroke need to be ruled out in younger patients.